Comparison of the Effectiveness of Nutritional Risk Score-2002 and Royal Free Hospital-Nutritional Prioritizing Tool Nutrition Screening Tools in Liver Cirrhosis - Calapkorur, Sema; Canaydin, Asli Onur; Can Sezgin, Gulten; Sahin, Habibe (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Malnutrition is a serious problem in patients with liver cirrhosis; therefore, it is recommended that nutritional screen ing should be performed regularly with appropriate nutritional screening tools (NSTs). This study aimed to compare the efficacy of the Nutritional Risk Score-2002 (NRS-2002) and Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT) NSTs in detecting malnutrition in liver cirrhosis patients. Materials and Methods: This study was conducted with cirrhotic patients (n = 149). The NRS-2002 and RFH-NPT scales were used to assess the nutritional status of patients, and anthropometric measurements were taken. Biochemical findings of patients were recorded. The Chronic Liver Disease Life Quality Scale 2.0 (CLDLQS 2.0) was used to determine the quality of life. Results: According to both NSTs, patients with nutritional risk had lower body weight, body mass index, albumin levels, higher C-reactive protein levels, and quality of life scores than patients without nutritional risk (P < .05). The sensitivity and specificity of the RFH-NPT were 91.5% and 63.3%, respectively. Albumin was more effective in predicting nutritional risk than other biochemical parameters. The RFH-NPT was found to be more correlated with biochemical parameters than NRS-2002. Conclusion: The RFH-NPT is highly effective in detecting malnutrition and correlates with biochemical parameters in cirrhotic patients. 16Cite this article as: Calapkorur S, Canaydin AO, Sezgin GC, Sahin H. Comparison of the effectiveness of Nutritional Risk Score-2002 and Royal Free Hospital-Nutritional Prioritizing Tool nutrition screening tools in liver cirrhosis. Turk J Gastroenterol. Published online November 21, 2025. doi:10.5152/tjg.2025.25632.